IGBO Version of the Older People’s Quality Of Life Questionnaire (OPQOL-35) Is Valid and Reliable: Cross-Cultural Adaptation and Validation - Ukamaka Gloria Mgbeojedo MSc; Chisom Cassandra Ekigbo BMR; Emmanuel Chiebuka Okoye PhD; Echezona Nelson Ekechukwu PhD; Adaora Justina Okemuo MSc; Chioma Nneka Ikele MSc; Christopher Olusanjo Akosile PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
To translate, cross-culturally adapt, and psychometrically evaluate the Older People’s Quality of Life Questionnaire (OPQOL-35) among the Igbo older adult population in Enugu State. The original English OPQOL-35 (E-OPQOL-35) was translated into Igbo language, synthesized, back translated, and subsequently subjected to expert panel review, pre-testing and cognitive debriefing interview. The final Igbo version (I-OPQOL-35) was tested for internal consistency, concurrent, and structural validities in a cross-sectional study of 115 consenting apparently healthy older adults that were conveniently recruited from Enugu State, at 0.05 level of significance. The Spearman correlation coefficients between the participants’ domain and total scores on the I-OPQOL-35 and E-OPQOL-35 (rho = .92-1.00) were excellent. The Mann–Whitney U test revealed no significant difference between corresponding scores in the E-OPQOL-35 and I-OPQOL-35 ( P  = .65-.94). The internal consistency coefficient of the I-OPQOL-35 was 0.78. The ceiling and floor effects were 0% respectively. The I-OPQOL-35 is therefore a valid and reliable instrument for the assessment of quality of life among Igbo older adults in Nigeria.